Developing a Game Model “Mysterious Card” to increase Students’ Motivation in Learning English - Rismawati; Muhammad; Suryati; Dewi (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2020)
Learning English is difficult for some elementary school students. Games can be used to develop students’ interest in learning English. This research will used a game namely mysterious card. The game combines snake and ladder games and flashcard. The object of this research was the fifth-grade students of an Islamic Elementary School in Mempawah. The method used was Research and Development (R&D). The data was collected using a questionnaire and interview, then it was analyzed quantitatively and qualitatively. The research result shows that the application of the mysterious card game model to the fifth-grade students of Islamic Elementary School is suitable in creating the English learning in a fun way in the class. Thus, the game model was also able to be used in increasing student’s motivation in learning English.